Community pharmacy staff motivations and barriers to working with mental health consumers. (27th July 2016) - Knox, Kathy; Hattingh, Laetitia; Wheeler, Amanda J.
Abstract: Background: Mental health is an Australian national priority area, yet evidence indicates pharmacy staff members focus more frequently on other chronic diseases. A need was identified to facilitate community pharmacy staff engagement with mental health initiatives. Aim: This study explored community pharmacy staff motivations and barriers to working with mental health consumers and carers. Method: A questionnaire assessing baseline attitudes, knowledge and skills towards mental illness was completed by 791 community pharmacy staff members. Participants rated their agreement with statements regarding factors that motivate them (11 items) or present a barrier to working with mental health consumers and carers (12 items) on a 7‐point Likert scale. Qualitative comments were invited. Results: In total, 465 pharmacists (58.8%) and 326 support staff (41.2%) completed the questionnaire. Statements reflecting motivations were strongly endorsed: 83% of participants agreed that they were motivated to work with mental health consumers and carers, and 96% agreed that community pharmacists are integral members of the healthcare team. The most frequently endorsed barriers related to lack of training to assist people and belief that consumers feel ashamed about their illness. Themes that emerged from qualitative comments identified staff skills and knowledge as both motivators and barriers. Conclusion: The findings identified that both pharmacists and pharmacy support staff required more training, confidence and practical strategies to support best practice in meeting the needs and expectations of mental health consumers and carers.